Fostering Engagement and Learning Outcomes: A Comparative Analysis of Ethnochemical and STEM-based Pedagogies for Chemistry Learning in Vocational High Schools - Khatimah, Maulidya Husnul; Chisbiyah, Lismi Animatul (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2024)
In contemporary education, the perceived difficulty of learning chemistry, attributed to its abstract nature, remains a challenge for many students. This difficulty is compounded by a notable lack of alignment between chemistry concepts and students’ daily experiences, despite the inherent relevance of chemistry to their everyday phenomena. Building on previous research affirming the efficacy of ethnochemical modules in enhancing student learning and achievement, this study investigates the suitability of a STEM-based approach for chemistry education, particularly in vocational high school. The research methodology employs a literature study method, utilizing the PICO(T) framework for keyword selection. A rigorous review and analysis of 15 from 94 scientific papers were conducted to glean insights into the effectiveness of these pedagogical approaches. The literature synthesis emphasizing the importance of cultural relevance, interactive module design, and active learning strategies in shaping students’ engagement and learning outcomes in chemistry education in vocational high school.DOI: 10.17977/jps.v12i12024p001